Prevalence and prognosis of prodromal Alzheimer's disease as assessed by magnetic resonance imaging and 18F‐fluorodeoxyglucose‐positron emission tomography in a community: reanalysis from the Osaki‐Tajiri Project. Issue 2 (26th June 2015) - Meguro, Kenichi; Akanuma, Kyoko; Meguro, Mitsue; Yamaguchi, Satoshi; Ishii, Hiroshi; Tashiro, Manabu
Abstract: Background: Dubois et al . proposed the criteria for prodromal Alzheimer's disease (AD) to detect dementia in its very early stage. Because detection requires magnetic resonance imaging and 18 F‐fluorodeoxyglucose‐positron emission tomography (PET), the prevalence and prognosis have not been fully investigated. Methods: Our database included 346 healthy participants (Clinical Dementia Rating (CDR) 0), 119 with questionable dementia (CDR 0.5), and 32 dementia participants (CDR 1+) and was applied to investigate the prevalence of prodromal AD. Forty‐four CDR 0.5 participants (37%) were randomly selected to undergo 18 F‐fluorodeoxyglucose‐PET. The same percentage was applied to select 128 CDR 0 and 12 CDR 1 + participants (total: n = 184) to calculate the prevalence. A neuroradiologist classified the PET images in a blinded manner based on the criteria of Silverman et al . Participants were considered to have prodromal AD if they exhibited 'parietal/temporal +/− frontal hypometabolism' (PET) with hippocampal atrophy (magnetic resonance imaging). Results: Eighteen CDR 0.5 participants (40.9%) met the criteria for prodromal AD, which was a prevalence rate of 9.8% among older adults aged ≥65 years. Thirteen prodromal AD participants (72%) converted to AD during the 5‐year follow‐up period. Discussion: The concept and criteria for prodromal AD are useful for predicting which subjects in a community will convert to AD.